Advanced chronic kidney disease among UK children. Issue 11 (22nd June 2022) - Plumb, Lucy; Magadi, Winnie; Casula, Anna; Reynolds, Ben C; Convery, Mairead; Haq, Shuman; Hegde, Shivaram; Lunn, Andrew; Malina, Michal; Morgan, Henry; Muorah, Mordi; Tyerman, Kay; et al.
Abstract : The UK Renal Registry currently collects information on UK children with kidney failure requiring long-term kidney replacement therapy (KRT), which supports disease surveillance and auditing of care and outcomes; however, data are limited on children with chronic kidney disease (CKD) not on KRT. Methods: In March 2020, all UK Paediatric Nephrology centres submitted data on children aged <16 years with severely reduced kidney function as of December 2019, defined as an estimated glomerular filtration rate <30 mL/min/1.73 m 2 . Results: In total, 1031 children had severe CKD, the majority of whom (80.7%) were on KRT. The overall prevalence was 81.2 (95% CI 76.3 to 86.3) per million of the age-related population. Conclusions: The prevalence of severe CKD among UK children is largely due to a high proportion of children on long-term KRT. Expanding data capture to include children with CKD before reaching failure will provide greater understanding of the CKD burden in childhood.